1988
DOI: 10.1002/bjs.1800750504
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of injection sclerotherapy in the management of 152 children with oesophageal varices

Abstract: A total of 152 consecutive children with oesophageal varices have been endoscopically reviewed since 1979. In all, 108 of these children presented with variceal bleeding which was managed by injection sclerotherapy. Variceal obliteration was achieved in 33 (92 per cent) children with extrahepatic portal hypertension and 54 (75 per cent) with intrahepatic portal hypertension. Prophylactic injection sclerotherapy was used to obliterate large varices in 11 children with no history of haemorrhage. Bleeding episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
5
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(124 citation statements)
references
References 43 publications
8
109
5
2
Order By: Relevance
“…1,2,[9][10][11][12] The percentage of patients (4.2%) who developed esophageal stricture in our EIS group is lower than reported (6% to 16%) in other studies of EXPVO treated by EIS. 1,2,[9][10][11][12] The relatively lower incidence of stricture in our study may be related to the use of primarily intravariceal injec- tion, smaller volume of the sclerosant used, and routine use of sucralfate gel or pantoprazole after endoscopic treatment.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…1,2,[9][10][11][12] The percentage of patients (4.2%) who developed esophageal stricture in our EIS group is lower than reported (6% to 16%) in other studies of EXPVO treated by EIS. 1,2,[9][10][11][12] The relatively lower incidence of stricture in our study may be related to the use of primarily intravariceal injec- tion, smaller volume of the sclerosant used, and routine use of sucralfate gel or pantoprazole after endoscopic treatment.…”
Section: Discussionmentioning
confidence: 89%
“…1,2 Bleeding from the esophageal varices is the most common presenting feature of EXPVO and is associated with significant morbidity. 1,3,4 Although optimal treatment for these patients is a matter of controversy, current therapeutic options include a variety of surgical procedures [5][6][7][8] or endoscopic injection sclerotherapy (EIS).…”
Section: E Xtrahepatic Portal Venous Obstruction (Expvo) Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum also varies from country to country. In the West, intrahepatic causes of portal hypertension are common in children, whereas in the East, portal hypertension in children is mainly due to extrahepatic portal venous obstruction [96][97][98][99][100][101][102][103]. Endoscopic screening is still the best option in children for detecting varices.…”
Section: Recommendationsmentioning
confidence: 99%
“…No wellestablished approaches exist for preprimary and early primary prophylaxis in children. At present, only a few studies have been reported on primary prophylaxis of variceal bleeding in children [101][102][103][104][105][106]. In one retrospective study, propanolol was used in children with portal hypertension for prevention of variceal bleeding [106].…”
Section: Recommendationsmentioning
confidence: 99%